A method for producing active micro powder by co-processing manganese slag with a boiling furnace
By using calcining additives to treat electrolytic manganese slag in a boiling furnace, the problems of high moisture content and release of harmful substances were solved, and high-active electrolytic manganese slag active fine powder was prepared, achieving the resource utilization of manganese slag and meeting the environmental protection requirements.
Patent Information
- Application Number
- CN202310241771.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-03-14
AI Technical Summary
How to effectively utilize electrolytic manganese slag to solve the problems of high moisture content, strong mobility and release of harmful substances.
The boiling furnace collaborative treatment method is adopted to mix the dried electrolytic manganese slag with a calcining additive, and high-temperature calcination and grinding to achieve ammonia nitrogen removal, manganese ion oxidation and sulfate decomposition, and finally prepare highly active electrolytic manganese slag active fine powder.
Through this method, the moisture content of electrolytic manganese slag is greatly reduced, and ammonia nitrogen, sulfate and manganese ions are all effectively treated. The prepared active powder has high gelling activity and is suitable for cement and concrete blending materials, achieving the resource utilization of manganese slag and meeting environmental protection requirements.
Smart Images

Figure CN116332535B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of resource utilization of industrial solid wastes, and in particular to a method for producing active micropowder by co-processing manganese slag with a boiling furnace. Background Art
[0002] Manganese plays a very important role in the national economic construction. The main method of producing metallic manganese is electrolysis. my country is the world's largest producer, consumer and exporter of electrolytic manganese, accounting for more than 98% of the global electrolytic manganese production. While the electrolytic manganese industry is developing, it is also facing huge environmental and resource pressures, among which the disposal of electrolytic manganese slag is particularly prominent.
[0003] Electrolytic manganese slag is a high-water content industrial solid waste produced after leaching of manganese ore during the production of electrolytic manganese metal. It contains a large amount of heavy metals and ammonia nitrogen and belongs to Class II general industrial solid waste. Electrolytic manganese slag has a high water content (25-28%) and fine particles (40-250μm). It has strong mobility and fluidity in the environment. Manganese slag contains hydrates such as calcium sulfate, manganese sulfate, ammonium sulfate and ammonium manganese sulfate. Under the action of its own water content and natural precipitation, it is easy to form leachate containing harmful substances such as ammonia nitrogen and metallic manganese ions.
[0004] At present, there are 120-130 million tons of electrolytic manganese slag stored in the open air in my country, and 10 million tons are newly discharged every year. With the increasing consumption of manganese ore, the mainstream grade of manganese ore has gradually decreased. Every 1t of metallic manganese is produced to produce 8-10t of electrolytic manganese slag. According to the characteristics of electrolytic manganese slag and environmental protection requirements, enterprises generally adopt the treatment method of building a slag field and storing it in a high dam, and then close the warehouse and reclaim it after the slag field is full. A lot of active exploration has been carried out at home and abroad on the resource utilization of electrolytic manganese slag, but most of the work is still in the laboratory exploration stage and needs further exploration and improvement. There is still no technology that can be applied on a large scale in actual production. How to effectively utilize electrolytic manganese slag is the current problem. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for producing active micropowder by co-processing manganese slag with a boiling furnace. The technical problem to be solved is to achieve ammonia nitrogen removal, manganese ion oxidation and sulfate decomposition through the treatment of the boiling furnace, and finally prepare highly active electrolytic manganese slag active micropowder.
[0006] The technical solution of the present invention is: a method for producing active micro powder by co-processing manganese slag with a boiling furnace, comprising:
[0007] The crushed electrolytic manganese slag is first dried, then mixed with a calcination aid and sent to a boiling furnace for calcination, and finally the calcined sample is ground; wherein the amount of the calcination aid added is 1-15% of the mass of the dried electrolytic manganese slag.
[0008] Preferably, the calcination aid is selected from at least one of boron oxide, aluminum oxide, yttrium oxide and calcium fluoride.
[0009] Preferably, the calcination aid is composed of the following components by mass percentage: 70-90% boron oxide and 10-30% aluminum oxide.
[0010] Preferably, the calcination aid is composed of the following components by mass percentage: 85-95% boron oxide and 5-15% yttrium oxide.
[0011] Preferably, the calcining aid is composed of the following components by mass percentage: 70-85% boron oxide, 10-20% aluminum oxide, and 5-10% calcium fluoride.
[0012] Preferably, the drying process is carried out at a temperature of 90-110° C., for a time of 10-120 min, and in an air atmosphere.
[0013] Preferably, the boiling gas in the boiling furnace is one of preheated air and oxygen.
[0014] Preferably, the temperature in the boiling furnace is maintained at 900-1300° C., and the calcination time is controlled at 0.5-8 hours.
[0015] Preferably, the calcination temperature is 950-1100° C. and the calcination time is 30-60 min.
[0016] Preferably, the calcined sample is ground in a ball mill or a vibration mill; the grinding time is 10-60 min; the ground sample is sieved with a square hole sieve with a fineness of 80 μm, and the sieve residue is within the range of 10.0%, and the powder under the sieve is the active micropowder of electrolytic manganese slag.
[0017] By means of the above technical solution, the method for producing active micro powder by co-processing manganese slag with a boiling furnace proposed by the present invention has at least the following advantages:
[0018] 1. In the present invention, by adding a calcining aid, the physical structure of the electrolytic manganese slag is changed in a high-temperature molten state. The introduction of the calcining aid can effectively reduce the viscosity of the melt and promote the melting of the crystals in the manganese slag, thereby effectively reducing the melting point of the electrolytic manganese slag. At the same time, the calcining aid can break the original skeleton and high-bond energy components in the electrolytic manganese slag, reduce the precipitation of crystals, and increase the glass content in the electrolytic manganese slag, thereby achieving the effect of improving the activity of the active micropowder of the electrolytic manganese slag.
[0019] 2. In the present invention, the drying treatment of the electrolytic manganese slag is carried out at a temperature between 90 and 110° C. At this stage, the adsorbed water and part of the crystallized water in the electrolytic manganese slag are removed, which greatly reduces the moisture content of the electrolytic manganese slag and improves the efficiency of subsequent high-temperature calcination; at the same time, the ammonia nitrogen in the electrolytic manganese slag will also be decomposed in large quantities during the drying process, avoiding the damage to the boiling furnace caused by the subsequent release.
[0020] 3. In the present invention, the calcined electrolytic manganese slag is ground, which destroys the SiO 2 The crystal structure of the active powder is changed, resulting in different degrees of crystal defects and smaller grain size, which is beneficial to improving the activity of the active powder. At the same time, grinding can increase the specific surface area of the active powder and stimulate the free energy on the surface of the active powder, which can improve its activity.
[0021] 4. The active micropowder of electrolytic manganese slag obtained by the method of the present invention has high gelling activity and can be used as cement admixture and concrete admixture, thus realizing the resource utilization of electrolytic manganese slag.
[0022] 5. The ammonia nitrogen and sulfate in the electrolytic manganese slag active powder obtained by the method of the present invention are greatly reduced compared with the electrolytic manganese slag, and the manganese ions are also solidified. The corresponding indicators in the leaching solution meet the requirements of Class I pollutants in the national standard "Integrated Wastewater Discharge Standard" (GB 8978). BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the XRD pattern of electrolytic manganese slag sample. DETAILED DESCRIPTION
[0024] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of the specific implementation method, structure, characteristics and effects of a method for producing active micropowder by co-processing manganese slag with a boiling furnace according to the present invention in combination with a preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0025] One embodiment of the present invention proposes a method for producing active micropowder by co-processing manganese slag with a boiling furnace, which includes: first drying the crushed electrolytic manganese slag, then mixing it with a calcination aid and sending it into a boiling furnace for calcination, and finally grinding the calcined sample; wherein the amount of the calcination aid added is 1-15% of the mass of the electrolytic manganese slag after drying.
[0026] The type of electrolytic manganese slag in this embodiment is not limited, including but not limited to acid leaching manganese slag, filter press manganese slag, and manganese sulfide slag.
[0027] When the amount of additive added is less than 1%, the expected effect cannot be achieved due to too little addition. When the amount of additive added is too much, the original glass network silicon-oxygen tetrahedron of the manganese slag is easily destroyed seriously. The excess additive and the broken bonds in the manganese slag form new minerals, which inhibit the gelling activity of the manganese slag.
[0028] By adding calcination aids, the physical structure (i.e. crystal structure) of electrolytic manganese slag is changed in a high-temperature molten state. The chemical bonds of silicon-oxygen tetrahedron and manganese-oxygen octahedron that should have been produced during the sintering process of electrolytic manganese slag are interrupted by calcination aids, making it difficult for crystals to precipitate, thus changing its physical structure.
[0029] The introduction of calcining aids can effectively reduce the viscosity of the melt and promote the melting of crystals in the manganese slag, thereby effectively reducing the melting point of electrolytic manganese slag. Calcination aids are used in the smelting industry and can form a low-temperature eutectic phenomenon with manganese slag in a molten state, thereby reducing the melting point of manganese slag.
[0030] At the same time, the calcining aid can break the original skeleton and high bond energy components in the electrolytic manganese slag, reduce the precipitation of crystals, increase the glass content in the electrolytic manganese slag, and achieve the effect of improving the activity index of the active micro powder of the electrolytic manganese slag. By adding the calcining aid, the proportion of manganese slag is reduced, the mineral content formed by manganese slag is reduced, and the introduced oxides together with the original silicon-oxygen tetrahedron in the manganese slag form a glass network structure, thereby increasing the glass phase content inside the manganese slag and forming amorphous minerals. The amorphous silicon oxide, aluminum oxide, etc. in the manganese slag react with calcium hydroxide to improve the hydration strength of cement.
[0031] In some embodiments, the calcination aid is selected from at least one of boron oxide, aluminum oxide, yttrium oxide, and calcium fluoride.
[0032] In some preferred embodiments, the calcination aid is composed of the following components by mass percentage: 70-90% boron oxide and 10-30% aluminum oxide.
[0033] In other preferred embodiments, the calcination aid is composed of the following components by mass percentage: 85-95% boron oxide and 5-15% yttrium oxide.
[0034] In some other preferred embodiments, the calcination aid is composed of the following components by mass percentage: 70-85% boron oxide, 10-20% aluminum oxide, and 5-10% calcium fluoride.
[0035] In some embodiments, the drying process is carried out at a temperature of 90-110° C., for a time of 10-120 min, and in an air atmosphere.
[0036] In some embodiments, the boiling gas in the boiling furnace is one of preheated air and oxygen.
[0037] In some embodiments, the temperature in the boiling furnace is maintained at 900-1300° C., and the calcination time is controlled at 0.5-8 hours.
[0038] Furthermore, the optimal calcination temperature is 950-1100°C, and the optimal calcination time is 30-60min.
[0039] Through drying and high-temperature calcination, the sulfate in the electrolytic manganese slag can be decomposed and Mn can be oxidized to MnO. 2 , ammonia nitrogen decomposition. The main component of soluble Mn in manganese slag is MnSO 4 , pure MnSO 4 It decomposes at 750~1100℃. Since manganese exists in multiple variable valence states, the thermal decomposition products of manganese sulfate at different temperatures are also different. In the specific experimental process, when the calcination temperature exceeds 900°C, the sulfur content in the electrolytic manganese slag drops significantly.
[0040] By adding calcining aids, the temperature of liquid phase appearance and the viscosity of liquid phase of electrolytic manganese slag can be reduced, which can not only reduce the calcining temperature and improve thermal efficiency, but also reduce the calcining time. The addition of calcining aids is also beneficial to increase the formation of glass phase in electrolytic manganese slag during calcination, and can reduce the amount of calcium hydroxide in the hydration product, which is helpful to improve the early and late hydration activity of electrolytic manganese slag.
[0041] In some embodiments, the grinding of the calcined sample is performed in a ball mill or a vibration mill.
[0042] In some embodiments, the grinding time of the calcined sample is 10-60 min.
[0043] In some embodiments, the ground sample is sieved with a square hole sieve with a fineness of 80 μm, and the sieve residue is within the range of 10.0%. The powder under the sieve is the active fine powder of electrolytic manganese slag.
[0044] Compared with the current storage method of electrolytic manganese slag in slag storage, the active fine powder of electrolytic manganese slag treated by the method of the present invention not only meets the environmental protection requirements, but also can be used as concrete admixture and cement admixture, thus realizing the high-value utilization of electrolytic manganese slag.
[0045] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0046] In the following examples of the present invention, unless otherwise specified, all reagents used can be purchased on the market, and unless otherwise specified, all methods involved are conventional methods.
[0047] Examples 1-3
[0048] (1) 100 g of the crushed electrolytic manganese slag was ground in a ball mill for 30 min, and sieved with a square mesh sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the residue under the sieve was ground as Example 1.
[0049] (2) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 100° C. for 60 min, taken out and sent to a ball mill for grinding for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue under the sieve was within the range of 10.0%, and the residue under the sieve was ground as Example 2.
[0050] (3) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 100° C. for 60 min, mixed with 15 g of boron oxide (mass ratio 15%), and then sent to a boiling furnace at 1050° C. for calcination for 40 min in an air atmosphere. The calcined manganese slag was ground in a ball mill for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the residue under the sieve was ground as Example 3.
[0051] (4) According to the national standard "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" (HJ 557)
[0052] The extracts of Examples 1-3 were prepared and then respectively determined according to the national standard "Water quality - Determination of ammonia nitrogen - salicylic acid spectrophotometry" (HJ 536), the national standard "Water quality - Inorganic anions (F - , Cl - 、NO 2- Br - 、NO 3- ,PO 4 3- 、SO 3 2- 、SO 4 2- The contents of ammonia nitrogen, sulfate and manganese ions in the leachates of Examples 1-3 were detected according to the national standard “Determination of 22 Metal Elements in Solid Waste by Inductively Coupled Plasma Atomic Emission Spectrometry” (HJ 781). The specific values are shown in Table 1.
[0053] Table 1 Contents of ammonia nitrogen, sulfate and manganese in the leaching solution
[0054]
[0055] pass Figure 1It can be seen that the electrolytic manganese slag in Example 1 contains SiO 2 and CaSO 4 ·2H 2 O characteristic peak, among which, CaSO 4 ·2H 2 O comes from CaMn(CO 3 ) 2 and CaCO 3 After reacting with sulfuric acid, the electrolytic manganese slag also contains a small amount of muscovite, albite, kaolinite and pyrite. After drying, obvious SiO 2 and CaSO 4 ·2H 2 O diffraction peak, while CaSO 4 ·2H 2 O diffraction peak is not obvious, indicating that CaSO 4 ·2H 2 O loses its crystal water and turns into gypsum when treated at high temperature; however, there is no obvious CaSO in the diffraction pattern of manganese slag after high temperature calcination. 4 ·2H 2 O and CaSO 4 The diffraction peaks indicate that the decomposition rate of sulfate is high during the heat treatment.
[0056] Embodiment 4-6
[0057] (1) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 100°C for 60 min, and then mixed with 15 g of boron oxide (mass ratio 15%) and sent to a boiling furnace at 1050°C in an air atmosphere for calcination for 40 min. The calcined manganese slag was ground in a ball mill for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the powder under the sieve was ground to obtain the prepared active micropowder.
[0058] (2) Take four portions of PO42.5 cement (100 kg), add active micropowder as a mixture, and set the addition amount to 0%, 5%, 10%, and 20% respectively. According to the national standard "Test Method for Cement Mortar Strength (ISO Method)" (GB / T 17671), cement mortar strength specimens are prepared and physical property tests are carried out to compare the physical properties of the examples and the control group. The compressive strength of each example and the blank group is shown in Table 2.
[0059] Table 2 Compressive strength
[0060]
[0061] Example 7
[0062] (1) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 110°C for 60 min, then mixed with 10 g of alumina (mass ratio 10%) and sent to a boiling furnace at 1100°C in an air atmosphere for calcination for 30 min. The calcined manganese slag was ground in a ball mill for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the powder under the sieve was ground to obtain the prepared active micropowder.
[0063] (2) Take 100 kg of PO42.5 cement, add active micropowder as a mixture, and set the addition amount to 20% respectively. According to the national standard "Test Method for Cement Mortar Strength (ISO Method)" (GB / T 17671), cement mortar strength specimens are prepared and physical property tests are carried out to compare the physical properties of the embodiment and the control group. The compressive strength of the embodiment and the blank group is shown in Table 3.
[0064] Table 3 Compressive strength
[0065]
[0066] Example 8
[0067] (1) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 95°C for 90 min, and then mixed with 14 g of aluminum oxide, boron oxide and 1 g of yttrium oxide (mass ratio 15%), and then calcined in a boiling furnace at 950°C under air atmosphere for 60 min. The calcined manganese slag was ground in a ball mill for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the powder under the sieve was ground to obtain the prepared active micropowder.
[0068] (2) Take 100 kg of PO42.5 cement, add active micropowder as a mixture, and set the addition amount to 20%. According to the national standard "Test Method for Cement Mortar Strength (ISO Method)" (GB / T 17671), cement mortar strength test pieces are made and physical property tests are carried out to compare the physical properties of the embodiment and the control group. The compressive strength of the embodiment and the blank group is shown in Table 4.
[0069] Table 4 Compressive strength
[0070]
[0071] Examples 9-16
[0072] (1) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 110°C for 30 min, and then mixed with the calcination aids in Table 5 and sent to a boiling furnace at 1000°C in an air atmosphere for calcination for 30 min. The calcined manganese slag was ground in a ball mill for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the powder under the sieve was ground to obtain the prepared active micropowder.
[0073] (2) Take 100 kg of PO42.5 cement, add active micropowder as a mixture, and set the addition amount to 20%. According to the national standard "Test Method for Cement Mortar Strength (ISO Method)" (GB / T 17671), cement mortar strength specimens were prepared and physical property tests were carried out to compare the physical properties of the embodiment and the control group. The compressive strength development of the embodiment and the blank group is shown in Table 5.
[0074] Table 5 Compressive strength
[0075]
[0076] Examples 17-18
[0077] (1) 100 g of the crushed electrolytic manganese slag was treated in a dry environment at 100°C for 60 min, and then mixed with 15 g of boron oxide (mass ratio 15%) and sent to a boiling furnace at 1050°C in an air atmosphere for calcination for 40 min. The calcined manganese slag was ground in a ball mill for 30 min, and sieved with a square hole sieve with a fineness of 80 μm. The residue on the sieve was within the range of 10.0%, and the powder under the sieve was ground to obtain the prepared active micropowder.
[0078] (2) The active powder of electrolytic manganese slag was used as the mineral admixture of electrolytic manganese sintering slag as concrete, and the amount (accounting for the total mass of cementitious materials) was 15% for Example 17, and 20% for Example 18. The concrete construction mix ratio selected strength grade C30, and its specific scheme concrete construction mix ratio is shown in Table 6. The slump and strength of the fresh concrete of Examples 17, 18 and the blank group mix ratio are shown in Table 7.
[0079] Table 6 Construction mix ratio scheme
[0080] Unit: kg / m 3
[0081]
[0082] Table 7 Concrete slump and strength
[0083]
[0084] It can be seen from Table 1 that the ammonia nitrogen content of the electrolytic manganese slag after drying treatment is greatly reduced, but the sulfate and manganese are not much different from the original slag; the active micropowder of the electrolytic manganese slag calcined at high temperature can remove ammonia nitrogen, oxidize manganese ions and decompose sulfate, thus achieving the harmlessness of the electrolytic manganese slag.
[0085] It can be seen from Table 2-5 that when the active powder of electrolytic manganese slag is used as a cement admixture, the strength is basically not affected when the dosage is below 20%, and it can meet the national standard limit.
[0086] It can be seen from Table 6 that the electrolytic manganese slag active powder prepared by mixing and calcining one-component, two-component, and three-component calcining aids with electrolytic manganese slag has a compressive strength ratio of significantly better than that of Examples 9, 10, and 11 at the same dosage, indicating that the effect of the two-component calcining aid is better than that of the one-component calcining aid, indicating that the two substances have a mutually promoting and synergistic effect. At the same time, the compressive strength ratio of Examples 15 and 16 is significantly better than that of Examples 12, 13, and 14. The above explanation shows that the effect of mixing two or more calcining aids is better than that of using them alone, and a highly active electrolytic manganese slag active powder can be obtained by appropriately adjusting the ratio between the calcining aids.
[0087] It can be seen from Table 7 that when the active powder of electrolytic manganese slag is used as a concrete admixture, the amount of the concrete (accounting for the total mass of cementitious materials) below 20% has basically no effect on the strength.
[0088] In the application of the present invention, the fluidized bed furnace uses coal powder with smaller particles for combustion, the combustion area is large and the coal powder stays in the furnace for a long time, which makes the heat storage in the furnace large and the combustion is relatively stable. Therefore, the use of the fluidized bed furnace to coordinate the treatment of electrolytic manganese slag can make the electrolytic manganese slag calcined more fully and save calcination time.
[0089] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0090] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for producing active micro powder by co-processing manganese slag with a boiling furnace, characterized in that: include: The crushed electrolytic manganese slag is first dried, then mixed with a calcination aid and sent to a fluidized bed furnace for calcination, and finally the calcined sample is ground; The amount of the calcining aid added is 1-15% of the mass of the electrolytic manganese slag after drying; The calcining aid is composed of the following components by mass percentage: 70-85% boron oxide, 10-20% aluminum oxide, and 5-10% calcium fluoride; The drying temperature is 90-110°C, the time is 10-120min, and the atmosphere is air; during the drying process, the ammonia nitrogen in the electrolytic manganese slag will decompose; By adding calcining aids, the chemical bonds of silicon-oxygen tetrahedron and manganese-oxygen octahedron produced during the sintering process of electrolytic manganese slag are broken in a high-temperature molten state, thereby changing the physical structure of the electrolytic manganese slag.
2. The method for producing active micro powder by co-processing manganese slag with a fluidized bed furnace according to claim 1, characterized in that: in, The boiling gas in the boiling furnace is one of preheated air and oxygen.
3. The method for producing active micro powder by co-processing manganese slag with a fluidized bed furnace according to claim 1, characterized in that: in, The temperature in the fluidized bed furnace is maintained at 900-1300°C, and the calcination time is controlled at 0.5-8 hours.
4. The method for producing active micro powder by co-processing manganese slag with a boiling furnace according to claim 3, characterized in that: in, The calcination temperature is 950-1100°C and the calcination time is 30-60min.
5. The method for producing active micro powder by co-processing manganese slag with a boiling furnace according to claim 1, characterized in that: in, The calcined sample is ground in a ball mill or a vibration mill; the grinding time is 10-60 minutes; the ground sample is sieved with a square hole sieve with a fineness of 80 μm, and the sieve residue is within the range of 10.0%. The powder under the sieve is the active micro powder of electrolytic manganese slag.
Citation Information
Patent Citations
Method for improving hydration activity of low-activity air-cooled blast furnace slag
CN108569855A